2009
DOI: 10.1007/s11558-009-9071-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of IMF programs on U.S. foreign direct investment in the developing world

Abstract: IMF, PRGF, SBA, EFF, U.S. Foreign Direct Investment, Catalytic finance, Developing World, F33, F35, P16, P45,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 59 publications
1
37
0
Order By: Relevance
“…Conditions are usually attached to the aid given to developing nations with some of them aimed at improving the economic and financial conditions of the recipient country. Research from [34] was carried out on 126 developing nations and found that overall IMF involvement in a certain country tends to encourage FDI from the United States of America. However, the amount of FDI flows into a host country depends on the specific IMF program taken.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conditions are usually attached to the aid given to developing nations with some of them aimed at improving the economic and financial conditions of the recipient country. Research from [34] was carried out on 126 developing nations and found that overall IMF involvement in a certain country tends to encourage FDI from the United States of America. However, the amount of FDI flows into a host country depends on the specific IMF program taken.…”
Section: Literature Reviewmentioning
confidence: 99%
“…13 For further details regarding problems related to Heckman-models without exclusion restrictions see Puhani (2000). 14 Alternatively, economic variables such as GDP, budget balance, inflation (Biglaiser and DeRouen 2010) …”
mentioning
confidence: 99%
“…Indeed, as we note in our theoretical discussion of political mandates, financial markets tend to impose pressures on developing countries to support more open markets. We control for IMF conditionality with a dummy variable for countries currently under an IMF extended fund facility or stand-by agreement, as these arrangements come with strict loan conditions (Biglaiser and DeRouen 2010). Additionally, global capital mobility can affect neoliberal economic policies.…”
Section: Methodsmentioning
confidence: 99%